2002
DOI: 10.1093/annonc/mdf337
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan: mechanisms of tumor resistance and novel strategies for modulating its activity

Abstract: Camptothecins are broad-spectrum anticancer drugs that specifically target DNA topoisomerase I (Topo I). The formation of a cleavable drug-Topo I-DNA complex results in lethal double-strand DNA breakage and cell death. However, de novo or acquired clinical resistance to camptothecins is common. Studies of the camptothecin analog irinotecan suggest the following general mechanisms of resistance: (i) variable levels of the enzymes involved in the conversion of irinotecan; (ii) reduced cellular accumulation from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
253
1
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(262 citation statements)
references
References 61 publications
4
253
1
4
Order By: Relevance
“…The combined treatment also reduced tumour cell proliferation. In agreement with previous data (Ohwada et al, 1996;Xu and Villalona-Calero, 2002), we found that SN-38 alone markedly inhibited HT-29 cell proliferation by arresting cells mainly at the G2/M phase and, to a lesser extent, at the S phase. AS602868 for its part only induced a modest arrest at the S phase, but in combination with SN38 increased the number of cells in both S and G2/M phases.…”
Section: Discussionsupporting
confidence: 93%
“…The combined treatment also reduced tumour cell proliferation. In agreement with previous data (Ohwada et al, 1996;Xu and Villalona-Calero, 2002), we found that SN-38 alone markedly inhibited HT-29 cell proliferation by arresting cells mainly at the G2/M phase and, to a lesser extent, at the S phase. AS602868 for its part only induced a modest arrest at the S phase, but in combination with SN38 increased the number of cells in both S and G2/M phases.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we have shown that proteasome-mediated TOP1 downregulation is one part of the TIP pathway possibly downstream of transcription collision between RNA polymerase and TOP1cc. Interestingly, Bortezomib, the first proteasome inhibitor tested in clinical trial, has the greatest efficacy when combined with other chemotherapeutic agents including the TOP1-targeting drug irinotecan at its low dosage [33,34]. Consistently, we have also reported that the proteasome inhibitor MG132 sensitized cells to CPT-induced cytotoxicity and apoptosis [23].…”
Section: The Cellular Processing Pathways Of Top1cc and Implicationsmentioning
confidence: 76%
“…Mechanisms of tumor resistance to the NK-cell-independent anti-cancer effects of CPT-11 have been reviewed previously. 10 Resistance to NK cell cytotoxicity can also develop, but may be overcome by using immunotherapies that activate multiple types of immune cells, and therefore utilize non-overlapping mechanisms to destroy the tumor cells. We have recently found that Sindbis/IL-12 induces the IFNg-dependent activation of peritoneal macrophages in ES2-bearing mice.…”
Section: Resultsmentioning
confidence: 99%